Analisis Location Quotient Sektor Petambangan Dan Penggalian Di Kabupaten Manokwari Provinsi Papua Barat - Juanita R. Horman (JFRES Journal of Fiscal and Regional Economy Studies, 2021)
Location quotient (LQ) is a technique used in determining a base sector in an area. This analysis is needed in regional development planning which is closely related to the economic policy of a region. The basic sector is a sector that has great potential in determining the direction of development. The purpose of this study is to estimate or identify which sectors are the base sectors reviewed based on the 2015-2020 GDRP. From the results of the study, based on GDRP there are 15 sectors that are the base sector of the existing 17 sectors, and two of them are non-base sectors. The non-basic sectors include the mining and quarrying sector, and the manufacturing sector.